2018
DOI: 10.1080/02646838.2018.1437896
|View full text |Cite
|
Sign up to set email alerts
|

Maternal burn-out: an exploratory study

Abstract: This research shows the need for further work on maternal burn-out to better understand and prevent this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 32 publications
4
24
1
9
Order By: Relevance
“…Research has shown that a wide range of factors can either slightly or greatly increase the vulnerability to parental burnout (for a review of risk and protective factors and their respective weights, see . Parents are at greater risk when they aim to be perfect parents (Kawamoto et al, 2018;Sorkkila & Aunola, 2020), are neurotic or lack emotion and stress management abilities (Le Vigouroux, Scola, Raes, Lebert et al, 2018), lack emotional or practical support from the co-parent (Lindström, Åman & Norberg, 2011;Mikolajczak, Raes, Avalosse, & Roskam, 2018) or from the social network more broadly (Séjourné, Sanchez-Rodriguez, Leboullenger, & Callahan, 2018), have poor child-rearing practices , have children with special needs that interfere with family life (Gérain & Zech, 2018;Norberg, 2007;Lindström, Åman, & Norberg, 2010), or work part-time or are stay-at-home parents (Lebert et al, 2018;Mehauden & Piraux, 2018).…”
Section: Who Develops Parental Burnout? Risk Factors and Etiological mentioning
confidence: 99%
“…Research has shown that a wide range of factors can either slightly or greatly increase the vulnerability to parental burnout (for a review of risk and protective factors and their respective weights, see . Parents are at greater risk when they aim to be perfect parents (Kawamoto et al, 2018;Sorkkila & Aunola, 2020), are neurotic or lack emotion and stress management abilities (Le Vigouroux, Scola, Raes, Lebert et al, 2018), lack emotional or practical support from the co-parent (Lindström, Åman & Norberg, 2011;Mikolajczak, Raes, Avalosse, & Roskam, 2018) or from the social network more broadly (Séjourné, Sanchez-Rodriguez, Leboullenger, & Callahan, 2018), have poor child-rearing practices , have children with special needs that interfere with family life (Gérain & Zech, 2018;Norberg, 2007;Lindström, Åman, & Norberg, 2010), or work part-time or are stay-at-home parents (Lebert et al, 2018;Mehauden & Piraux, 2018).…”
Section: Who Develops Parental Burnout? Risk Factors and Etiological mentioning
confidence: 99%
“…Double-duty caregivers – being a formal and informal caregiver at the same time – are at higher risk of professional burnout than work-only caregivers (Häusler et al, 2017; DePasquale et al, 2018). In the same way, being an informal caregiver has been shown to increase the chances of parental burnout (Lindström et al, 2011; Gérain and Zech, 2018; Séjourné et al, 2018). The informal caregiving role thus seems to affect the caregiver’s other roles.…”
Section: Introductionmentioning
confidence: 97%
“…Beyond psychometric research, most efforts have been devoted to better understanding the risk factors for parental burnout. Findings have shown that parents are at greatest risk when they aim to be perfect parents (Kawamoto, Furutani, & Alimardani, 2018), are neurotic or lack emotion and stress-management abilities (Lebert-Charron, Dorard, Boujut, & Wendland, 2018; Le Vigouroux, Scola, Raes, Mikolajczak, & Roskam, 2017; Mikolajczak, Raes, Avalosse, & Roskam, 2018), lack emotional or practical support from the coparent or from the social network more broadly (Lindström et al, 2011; Mikolajczak, Raes, et al, 2018; Séjourné, Sanchez-Rodriguez, Leboullenger, & Callahan, 2018), have poor child-rearing practices (Mikolajczak, Raes, et al, 2018), have children with special needs that interfere with family life (Gérain & Zech, 2018; Lindahl Norberg, 2007; Lindström et al, 2010), or work part-time or are stay-at-home parents (Lebert-Charron, et al, 2018; Mehauden & Piraux, 2018; for a review of risk and protection factors for parental burnout and their respective weights, see Mikolajczak & Roskam, 2018). Researchers know much less about the consequences of parental burnout, but what is known suggests that parental burnout is a serious condition with pervasive effects on the parent (increase in addictive behaviors, sleep disorders, and family escape and suicidal ideations), on the couple (e.g., conflicts, adultery), and on the children (child neglect and violence; Mikolajczak, Brianda, Avalosse, & Roskam, 2018; Mikolajczak, Gross, & Roskam, 2019).…”
mentioning
confidence: 99%